Rumours - Sydney Dance Company ([Sydney] : Sydney Dance Company, 1981)
Poster advertising the release of Sydney Dance Company's film of their performance of Graeme Murphy's "Rumours. Features black and white image of 12 dancers in a circle, one of whom appears in the centre with a radio in her mouth (her lips have been coloured pink). "Sydney Dance Company present an archival film of" appears at head of title. "An Australia Council film produced in association with Sentry Insurance" appears in the lower right corner along with the company's logo.
Caption title.
Also available online
Keywords: Murphy, Graeme, -- 1950- -- Posters; Sydney Dance Company -- Posters; Dance posters -- New South Wales -- Sydney; Posters, Australian; Australia -- Posters; Australian